(untitled) (Herald of the National Children’s Medical Center, 2025)
The postoperative period in children who have undergone brain tumor surgeries requires precise and comprehensive intensive therapy. The primary objectives include monitoring and stabilizing intracranial pressure (ICP), ensuring adequate sedation, regulating neurovegetative functions, and preventing complications. In children with neuro-oncological conditions, the unique brain physiology necessitates careful selection of pharmacological treatment and monitoring, including the use of consciousness assessment scales and specialized pressure sensors.